Social Support and Work in Italy: The Needs of Workers and the Role of Unions After the COVID-19 Pandemic - Sergio Cecchi; Gosetti, Giorgio; Tronca, Luigi (Italian Sociological Review, 2025)
This article presents some of the results of the PRIN 2022 research project “Social capital as resource of care practice in Italy: Caregiving and social support in pandemic time”. In particular, this article presents the results of the part of the research dedicated to the issue of social support, which consists of the support actually deriving from social relationships, with reference to individuals in specific working conditions. This essay aims to report on the qualitative analysis carried out, which focused primarily on the relationship between working conditions and social support networks in Italy from two conceptual dimensions that are particularly relevant in the post-pandemic period: the first concerns the polarisation of the labour market between those at the top of the social stratification (permanent workers with high levels of education and good professional qualifications) and those at the bottom of the social stratification (temporary workers with low levels of education and low professional qualifications). The second dimension concerns the distinction between those who have been unemployed at least once in the 12 months prior to the interview (those who have benefited from the wage supplementation scheme and those who have not benefited from it). An additional source of information taken into consideration is the perspective of certain regional trade union secretaries. The study presented here was conducted according to the structural interactionist approach, which posits that the networks within which subjects find themselves are, at the same time, both a constraint and an emerging effect of their actions.